Guidelines for Learning to Shooting Video for Sale Online in the Digital Age - Nonthamand, Narin (Journal of Education Studies, Chulalongkorn University, 2020)
Recording a video of important events to retain emotions and feelings is one of the best way to express ideas. Comparing to past practices, the person recording should first learn basic functions such as video resolution, video format, frame rate, composition, camera movement, equipment used for shooting, composition techniques for shooting, file management, video editing, audio editing and visual effects including the trend of videos in the online market. In the digital era, video makers can find various online sources such as websites, social media, online courses published by universities or education agencies, self-learning programs and MOOC which has become popular today. Even in the classroom, teachers should encourage students to learn and experiment independently, which will enable learners to gain knowledge from practice After learning about production, learners should also pick up more about uploading the video to the system for sale on different websites, including the terms and conditions of selling videos online. Different websites may have varying terms and conditions for buying and selling videos. Learners should also study the terms and conditions throughly to enhance their learning process in the digital age. Those who love making videos may be pleased to know they may earn an income doing what they love.